Physical oceanography during RV POLARSTERN cruise PS86 (ARK-XXVIII/3 AURORA) - Christian Mertens (PANGAEA, 2025)
During Polarstern cruise PS86 in the Arctic Ocean (7 July - 3 August, 2014) Conductivity-temperature-depth (CTD) casts were carried out using a Sea-Bird Electronics, Inc. SBE 911plus system (AWI Bremerhaven) that was equipped with double temperature and conductivity sensors. Additionally a custom build Seapoint Turbidity Meter (5x normal gain), a transmissometer and two redox potential (Eh) sensors were used to identify hydrothermal plume signals in the water column. The first Eh-sensor was built by Koichi Nakamura (AIST, Japan) and the second one was a CTD version of the MAPR Eh sensor build at NOAA PMEL.